The use and readability of mental health self-help in Scottish prisons. Issue 3 (4th May 2017) - Dunlop, L. C. D.; Bennett, Daniel M.
Abstract: Prisoners are at higher risk of mental health problems than people in the general community. One possible way of optimising mental health care resources in prisons is to offer self-help materials. In order for these to be effective, they must be appropriate for the reading ability of the patient. This study aimed to determine, by way of a survey distributed to Scottish mental health care teams, how self-help resources are being used currently in the Scottish prison system, and to analyse the materials using four different readability tools: FRE, FKGL, SMOG and the Drivel Defence programme. It was found that there is currently widespread provision of self-help to Scottish prisoners; however, only 53% of these materials are suitable for the quoted average prisoner reading age. Mental health practitioners should be aware of this when providing self-help to patients, and consider easy-read options where available.